Electroplating Industry Effluent Induced Modulation Of Aminotransferase Activity In The Freshwater teleost Fish Mystus punctata - Palanisamy, P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Electroplating industry effluent exposure (1%) for 48 hr increased the AlAT and AAT contents in the brain, gill, liver and muscle of Mystus punctata. Both protein and carbohydrate metabolism was affected. Alanine aminotransferase (AAT E.C. 2.6.1.2) and aspartate aminotransferase (AAT E.C. 2.6.1.1) play a crucial role in transamination reactions and can be used as potential biomarkers to indicate hepatotoxicity and cellular damage.